Analisis Keselamatan dan Kesehatan Kerja Bengkel dan Laboraturium Jurusan Pendidikan Teknik Elektronika dan Informatika FT UNY - Wulandari, Bekti (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2018)
This research was conducted to describe planning, implementation, and evaluation of Occupational Health and Safety (OHS) in laboratory and workshop of Electronic Engineering and Informatics Department FT UNY. This research is a non-experimental quantitative research with descriptive approach method. Descriptive research is a study conducted on independent variables, without making comparisons or connecting with other variables, especially regarding OHS. This study aims to obtain information or description of OHS in the laboratory and workshop of Electronic Engineering and Informatics Department, Engineering Faculty, Yogyakarta State University. This research is only limited to describe that found in data retrieval. The results of this study indicate that the OHS System in the laboratory and workshop of Electronic Engineering and Information Technology Department of Engineering Faculty, Yogyakarta State University still needs to be improved. OHS planning in those places still needs to be improved to achieve effectiveness. Meanwhile, the implementation of OHS in the laboratory and workshop still needs to be improved. While the evaluation of OHS in the laboratory and workshop needs to be done continuously. In addition, it can be included that the factors of administration, supervision, and improvement of OHS culture needs to be done in order to achieve a systematic OHS Management System.